Glycan-lectin interactions in cancer and viral infections and how to disrupt them - Kremsreiter, Stefanie; Kröll, Ann-Sophie; Weinberger, Katharina; Böhm, Heike (International journal of molecular sciences, 2021)
Glycan-lectin interactions play an essential role in different cellular processes. One of their main functions is involvement in the immune response to pathogens or inflammation. However, cancer cells and viruses have adapted to avail themselves of these interactions. By displaying specific glycosylation structures, they are able to bind to lectins, thus promoting pathogenesis. While glycan-lectin interactions promote tumor progression, metastasis, and/or chemoresistance in cancer, in viral infections they are important for viral entry, release, and/or immune escape. For several years now, a growing number of investigations have been devoted to clarifying the role of glycan-lectin interactions in cancer and viral infections. Various overviews have already summarized and highlighted their findings. In this review, we consider the interactions of the lectins MGL, DC-SIGN, selectins, and galectins in both cancer and viral infections together. A possible transfer of ways to target and disrupt them might lead to new therapeutic approaches in different pathological backgrounds.
Gesehen am 18.11.2021